Cardiac papillary fibroelastoma as a cause of acute coronary syndrome. Issue 5 (November 2022) - Chau, Anh Thi Ngoc; Nguyen, Quang Hien; Pham, Hoang Nhat; Vo, Mike; Huynh, Ba Duong; Pham, Nguyen Hai Nam; Tran, Viet Nghi; Phan, Vien; Ha, Quang Dat; Pham, Dat; Pham, Thien; Do, Dan; et al.
Abstract: Cardiac papillary fibroelastoma (CPF) is a benign primary cardiac neoplasm, commonly found in men and above 40 years old. The clinical presentation of CPF ranges from asymptomatic to embolism-related complications such as stroke, myocardial ischemia, infarction, or ventricular fibrillation. Acute coronary syndrome is a rare complication of CPF, which was reported only in a few cases in medical literature. Hence, we report a case of a 50-year-old female with a CPF on the right coronary cusp of the aortic valve diagnosed with multi-modality imaging with definitive diagnosis through histopathologic confirmation. The patient presented with acute onset of fatigue, diaphoresis, and vomiting. Initial electrocardiogram (ECG) demonstrated T wave inversion in aVL. Repeated ECG two hours later showed persistent T wave inversion in aVL with new T wave inversions in lead I and ST depression in V2-V6. Troponin levels were elevated from 3.6 ng/L to 1503 ng/L but the patient did not report chest pain, abdominal pain, or dyspnea. Computed tomography coronary angiography did not show any significant coronary stenosis but revealed a low attenuation node with 7 × 6 mm in dimension attached to the right coronary cusp of the aortic valve. Treatment was discussed among a multidisciplinary team and the CPF was surgically removed. Learning objective: Acute coronary syndrome is a rare, but potentially fatal complication of cardiac papillary fibroelastoma (CPF). Multi-modality imaging is valuable in delineating the evaluation of exact position, dimensions, nature of cardiac masses, diagnostic workup, and preliminary assessment before the surgery. There are no clear guidelines for the treatment of CPF.